Ceramide Aminoethylphosphonate as a New Molecular Target for Pore-Forming Aegerolysin-Based Protein Complexes - Balbi, Teresa; Trenti, Francesco; Panevska, Anastasija; Bajc, Gregor; Guella, Graziano; Ciacci, Caterina; Canonico, Barbara; Canesi, Laura; Sepčić, Kristina (Frontiers in Molecular Biosciences, 2022)
Ostreolysin A6 (OlyA6) is a 15 kDa protein produced by the oyster mushroom (Pleurotus ostreatus). It belongs to the aegerolysin family of proteins and binds with high affinity to the insect-specific membrane sphingolipid, ceramide phosphoethanolamine (CPE). In concert with its partnering protein with the membrane-attack-complex/perforin domain, pleurotolysin B (PlyB), OlyA6 can form bicomponent 13-meric transmembrane pores in artificial and biological membranes containing the aegerolysin lipid receptor, CPE. This pore formation is the main underlaying molecular mechanism of potent and selective insecticidal activity of OlyA6/PlyB complexes against two economically important coleopteran plant pests: the western corn rootworm and the Colorado potato beetle. In contrast to insects, the main sphingolipid in cell membranes of marine invertebrates (i.e. molluscs and cnidarians) is ceramide aminoethylphosphonate (CAEP), a CPE analogue built on a phosphono rather than the usual phosphate group in its polar head. Our targeted lipidomic analyses of the immune cells (hemocytes) of the marine bivalve, the mussel Mytilus galloprovincialis, confirmed the presence of 29.0 mol% CAEP followed by 36.4 mol% of phosphatidylcholine and 34.6 mol% of phosphatidylethanolamine. Further experiments showed the potent binding of OlyA6 to artificial lipid vesicles supplemented with mussel CAEP, and strong lysis of these vesicles by the OlyA6/PlyB mixture. In Mytilus haemocytes, short term exposure (max. 1h) to the OlyA6/PlyB mixture induced lysosomal membrane destabilization, decreased phagocytic activity, increased Annexin V binding and oxyradical production, and decreased levels of reduced glutathione, indicating rapid damage of endo-lysosomal and plasma membranes and oxidative stress. Our data suggest CAEP as a novel high-affinity receptor for OlyA6 and a target for cytolytic OlyA6/PlyB complexes.